1971
DOI: 10.1017/s0043174500050645
|View full text |Cite
|
Sign up to set email alerts
|

Topical Applications of DSMA and MSMA in Irrigated Cotton

Abstract: Single topical applications of monosodium methanearsonate (MSMA) affected cotton (Gossypium hirsutumL.) growth more than did similar disodium methanearsonate (DSMA) applications. There was usually no difference in yield among rates and dates with single applications of DSMA. Single applications of MSMA at later dates and higher rates reduced yields. Repeated topical applications of MSMA reduced yields and affected boll weight, lint percentage, number of seed per boll, and fiber fineness as compared with these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…However, addition of fluometuron antagonizes activity of these herbicides (8). Early research with topical applications of MSMA indicated that repeated applications affected cotton more than a single application and that applications late in the growing season affected cotton more than early applications (1,2). Baker et al (3) reported that a single application of MSMA over the top of 10-cm cotton was valuable when weed infestations were severe enough to reduce cotton yield.…”
Section: Introductionmentioning
confidence: 99%
“…However, addition of fluometuron antagonizes activity of these herbicides (8). Early research with topical applications of MSMA indicated that repeated applications affected cotton more than a single application and that applications late in the growing season affected cotton more than early applications (1,2). Baker et al (3) reported that a single application of MSMA over the top of 10-cm cotton was valuable when weed infestations were severe enough to reduce cotton yield.…”
Section: Introductionmentioning
confidence: 99%
“…MSMA injury symptoms from topical applications are first seen on the leaves, petioles, and stems. Leaves initially become dark blue-green and higher rates may eventually cause foliage burning and necrosis (Arle and Hamilton 1971;Snipes and Byrd 1994). Petioles and stems redden while temporary stunting may occur (Arle and Hamilton 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves initially become dark blue-green and higher rates may eventually cause foliage burning and necrosis (Arle and Hamilton 1971;Snipes and Byrd 1994). Petioles and stems redden while temporary stunting may occur (Arle and Hamilton 1971). Unstressed cotton generally can overcome the discoloration, foliage burn, and stunting 0 5 15 7 7 5 5 6 6 9 8 20 12 9 14 11 5 8 6 1 6 12 9 34 Totals 39 54 59 68 under favorable conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations